The "Valva Cerebri": Morphometry, Topographic Anatomy and Histology of the Rhomboid Membrane at the Craniocervical Junction. Issue 1 (8th September 2019) - Kurucz, Peter; Meszaros, Cintia; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo
Abstract : The arachnoid membranes' anatomy is a controversial topic in the literature, and the rhomboid membrane at the craniovertebral junction is an element of this system that has been described poorly. Hence, the objective of our study was to examine this membrane's anatomy and histology. A total of 45 fresh formalin‐fixed human cadaveric heads were examined, and anatomic dissections and histologic examinations using standard staining methods were performed. The membrane was found to be a constant structure. It has a rhomboid shape and is located on the medulla oblongata and upper cervical spine's ventral surface within the subarachnoid space. Its average craniocaudal length is 49 mm and the short axis is 26 mm. The cranial apex is attached to the vertebral arteries' junction, and the caudal apex reaches the level of C4. The lateral apices are attached to the dura mater at the level of the denticulate ligament's second insertion. The C1 spinal nerves perforate the membrane, while the C2 roots are located dorsal to it. The membrane is attached strongly to the underlying pia mater. Histologically, it has a typical arachnoid structure, in which its adhesions to the vertebral arteries as well as to the pia mater could be verified histologically. This is the first detailed examination of the rhomboid membrane. Our results suggest that the membrane serves a valve‐like function between the spinal and cranial subarachnoid spaces. Based on our findings, further hydrodynamic studies should clarify the membrane's physiological role. Clin. Anat. 32:56–65, 2019. © 2019 Wiley Periodicals, Inc.